The Effect of Kahoot toward Students’ Reading Comprehension at the Tenth Grade Students of SMAN 8 Muaro jambi - Rimeira Nadya Pratiwi; Khidayatul Munawwaroh; Ridho Praja Dinata (JELT: Journal of English Language Teaching, 2023)
This study aimed to find out whether or not there was any significant effect of kahoot toward students’ reading comprehension at tenth grade students of SMAN 8 Muaro Jambi. This research used quantitative research method with quasi-experimental research design which implicated experimental class and control class. The total population in this research was tenth grade students of SMAN 8 Muaro Jambi which consisted of 253 students. The samples of this research were chosen by using cluster sampling. The samples were divided into two classes, experimental class which consisted of 35 students and control class which consisted of 36 students. The technique of data collection in this research was pre-test, treatment, and post-test. The data were analyzed by using t-test. The researcher found that the mean score of pre-test at experimental class was 61,85 and the post-test was 81,71. Meanwhile the mean score of pre-test at experimental class was 60,00 and the post-test was 70,13. The result of t-test analysis presented that observation was higher than t-table (7,75 > 1,994). Therefore, H1 was accepted and H0 was rejected. As the result, there was any significant effect of kahoot toward students’ reading comprehension at tenth grade students of SMAN 8 Muaro Jambi